BEDA EFEKTIVITAS ANTARA HOLD RELAX DAN CONTRACT RELAX TERHADAP PENAMBAHAN RANGE OF MOTION (ROM) SENDI LUTUT AKIBAT OSTEOARTHRITIS DI RS.BHAYANGKARA - Muhammad Awal; Hendrik Hendrik (Media Fisioterapi Politeknik Kesehatan Makassar, 2020)
Osteoarthritis is a joint disorder that can cause limitations in joint motion which can be overcome by providing active and passive exercises.This research is a quasi-experimental study with a Pre Test – Post Test two group research design. This study aims to determine the effectiveness of hold relax and contract relax in increasing the range of motion (ROM) of the knee joint due to Osteoarthritis. This research was conducted at the Physiotherapy Clinic of the Hospital Bhayangkara with the population are all Osteoarthritis patients who visit the hospital. Bhayangkara Makassar during the study, using a purposive sampling method to obtain a total sample of 10 people based on inclusion criteria aged 45-65 years.The results of the paired t test in the hold relax group obtained a value of p = 0.025 <0.05 and in the contract relax group obtained a value of p = 0.099 > 0.05 while based on the results of the independent test between the hold relax group and the contract relax group showed that it was not significant where the p value = 0.305 > 0.05. Conclusion Hold relax and Contract relax have the same effect on increasing the value of knee joint ROM in Osteoarthritis patients, there is no significant effect on the addition of knee joint ROM in Osteoarthritis patients between the treatment groups. Keywords : Hold relax, Contract relax, knee joint ROM, Osteoarthritis